A simple end-point assay for calcium channel activity. (September 2018) - Chandrika, Arunkumar Renganathan; Steephan, Mathew; Raveendran Nair, Rajeevkumar; Sudarsana Devi, Suma Priya; Kumar, Mantosh; Paul, Soumya; Madhavan, Mayadevi; Omkumar, Ramakrishnapillai V.
Graphical abstract: Highlights: Novel end-point detection based method for intracellular calcium sensing. Technically simple to perform, less expensive and adaptable to high throughput. Signal shows quantitative relationship to cellular calcium concentration. Utility demonstrated by detecting activities of multiple calcium channels. Calcium sensor vector and stable cell line with calcium sensor proteins developed. Abstract: Cellular calcium signaling events are transient. Hence they are observed in real time using fluorescence imaging or electrophysiological methods that require sophisticated instrumentation and specialized skills. For high throughput assays simple and inexpensive techniques are desirable. Many calcium channels that serve as drug targets have subtypes arising from diverse subunit combinations. These need to be targeted selectively for achieving efficacy and for avoiding side effects in therapies. This in turn increases the number of calcium channels that act as drug targets. We report a novel method for intracellular calcium sensing that utilizes the calcium dependent stable interaction between CaM kinase II (CaMKII) and its ligands such as the NMDA receptor subunit GluN2B. The CaMKII-GluN2B complex formed persists as a memory of the transient increase in calcium. In a cell-based assay system GFP-α-CaMKII expressed in the cytosol responds to calcium by translocating towards GluN2B sequence motif exogenously expressed on mitochondria or endoplasmic reticulum. The resulting punctate fluorescence pattern serves as the signal for intracellular calcium release. The pattern is stable, unaffected by sample processing and is observable without real time imaging. The activities of calcium channel proteins heterologously expressed in HEK-293 cells were detected with specificity using this technique. A calcium sensor vector and a calcium sensor cell line were developed as tools to perform this technique. This technique being simple and less expensive could significantly facilitate high throughput screening in calcium channel drug discovery.